2021
DOI: 10.3389/fimmu.2021.624703
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Role of Tenascin-C in Myocarditis and Inflammatory Cardiomyopathy

Abstract: Accumulating evidence suggests that the breakdown of immune tolerance plays an important role in the development of myocarditis triggered by cardiotropic microbial infections. Genetic deletion of immune checkpoint molecules that are crucial for maintaining self-tolerance causes spontaneous myocarditis in mice, and cancer treatment with immune checkpoint inhibitors can induce myocarditis in humans. These results suggest that the loss of immune tolerance results in myocarditis. The tissue microenvironment influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…SDC4 was expressed by RPE cells, fibroblasts and endothelial cells in the scRNA-seq data ( Figure 4F ) and upregulated with age in the bulk data ( Figure 4E ). Changes in tenascin expression have been previously related to development and aging ( Choi et al, 2020 ; Matsumoto and Aoki, 2020 ) as well as to pathologic conditions such as cancer, inflammation and fibrosis ( Albacete-Albacete et al, 2021 ; Tajiri et al, 2021 ). Disruption of the tenascin pathway also results in promoting inflammatory processes and angiogenesis ( Kobayashi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…SDC4 was expressed by RPE cells, fibroblasts and endothelial cells in the scRNA-seq data ( Figure 4F ) and upregulated with age in the bulk data ( Figure 4E ). Changes in tenascin expression have been previously related to development and aging ( Choi et al, 2020 ; Matsumoto and Aoki, 2020 ) as well as to pathologic conditions such as cancer, inflammation and fibrosis ( Albacete-Albacete et al, 2021 ; Tajiri et al, 2021 ). Disruption of the tenascin pathway also results in promoting inflammatory processes and angiogenesis ( Kobayashi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…TNC may trigger inflammation [ 75 ] as a DAMP molecule and amplify the inflammatory responses of macrophages by creating a positive feedback loop [ 13 , 91 ], as discussed in an earlier section. Furthermore, TNC activates DCs to generate pathogenic autoreactive T cells and forms an important link between innate and acquired immunity [ 55 , 138 ]. DCs stimulated by TNC have been shown to produce various proinflammatory cytokines, including IL-6, which, in turn, induce naïve CD4+ T cells to differentiate into Th17 cells.…”
Section: Myocarditismentioning
confidence: 99%
“…found that TNC thriving was responsible for neuronal apoptosis and inflammation after subarachnoid hemorrhage [ 37 ]. Later, TNC was reported to play a immunomodulatory role in the inflammation-driven cardiomyopathy [ 38 ]. Mitochondria play a role in cell apoptosis by regulating the release of cytochrome C and ROS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%